English Language Variation of Tourist Guide and Local Souvenir Seller: A Case Study of Tigarihit Tourism Village - Booni Tauhid; Syahrul Syahrul; Muhammad Zulfan (International Journal Labs, 2024)
This study investigates the contribution of English education and the variations in English conversation between tourist guides and shopkeepers with international tourists in Tiga Rihit Tourism Village, Kampung Warna Warni, Simalungun Regency. This research uses a qualitative approach by collecting data through interviews, observation, and documentation. Random four respondents were interviewed for this transcript, they are Indonesians who work as tourist guides and local souvenir sellers. Segmental attributes of English variation are explored in various aspects, such as 1) standard and non-standard English, 2) grammatical variations, 3) omissions, and 4) repetitions. The positive impacts of English include increasing employment opportunities, increasing income, and improving people's quality of life. This study shows that in terms of education, the use of English also has an important role in improving the quality of education in the Tiga Rihit Tourism Village. The use of English also has an important role in improving the quality of education in the Tiga Rihit Tourism Village, Kampung Warna Warni, Simalungun Regency. English is used to increase community insight and knowledge and improve the quality of learning in schools in the village. Variations that occur in conversations carried out by tour guides and souvenir sellers include the use of non-standard English, grammatical errors, word omissions, and word repetition. Therefore, the use of English is expected to broaden the horizons and knowledge of people in the village. The English variation in conversations by Asian tourists is similar to Indonesian tourist guides and local souvenir sellers, wherein nonstandard English, repletion, and omission can be found.